Experimental investigation on the heat transfer performance of MHTHS using ethylene glycol-based nanofluids - Sriharan, G.; Harikrishnan, S.; Kalaiselvam, S.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Springer, 2021)
Experimental investigation on the heat transfer characteristics of the nanofluids passing through mini hexagonal tube heat sink (MHTHS) was accomplished. Al2O3-EG, CuO-EG, and SiO2-EG nanofluids with volume fraction ranging from 0.01 to 0.04% were chosen in the present study. The dispersion of nanoparticles in ethylene glycol (EG) was used as the working fluids. The volume flow rate of nanofluids flow through the hexagonal tube side was varied from 15 to 50 L h(-1), and the hot deionized water in mini passage side was kept constant at a volume flow rate of 30 L h(-1). The heat transfer characteristics of nanofluids were studied with the concentration of nanoparticles in base fluid and effect of Reynolds number. The heat transfer coefficient of MHTHS was measured under fully developed laminar and turbulent flow conditions. Based on the experimental data, it was observed that thermal conductivity, heat transfer coefficient, and Nusselt number of CuO-EG nanofluid were found to be higher when compared to other two nanofluids. The thermal conductivity of nanofluids was enhanced with an increase in concentration of nanoparticles in EG. The enhancement in heat transfer coefficient of nanofluid was achieved at higher turbulence in turbulent flow. It was due to stable dispersion of nanoparticles in EG. Therefore, the enhancement in heat transfer coefficient was found to be 36%, 32%, and 22% for CuO-EG, Al2O3-EG, and SiO2-EG nanofluid, respectively, at the concentration of 0.04 vol%. At higher Reynolds number, the agglomeration of nanoparticles decreases. Hence, it caused a decrease in boundary layer thickness which leads to an increase in the heat transfer-enhanced Nusselt number. The friction factor of SiO2-EG nanofluid was found to be lower in turbulent flow regime, and furthermore, it had no substantial effect in laminar flow regime.
Keywords: Thermal conductivity; Heat transfer coefficient; MHTHS; Reynolds number; Nusselt number; Nanofluid